THE USE OF MULTIMODALITY TREATMENT FOR AN ATYPICAL, RECURRENT AND AGGRESSIVE MEDULLARY THYROID CANCER - Arcellana, Anna Elvira; Sarsagat, Jim Paulo; Magnaye, Franz Michael; Hernandez, Aylmer Rex; San Juan, Michael; Almanon, Christelle; Crisostomo, Benedict; Cañal, Johanna Patricia; Isip-Tan, Iris Thiele (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Medullary thyroid cancer is a rare type of cancer of neuroendocrine origin, comprising about 1 to 3% of all types of thyroid cancers. Its clinical presentation is a complex spectrum. We present an extremely rare case of a calcitonin-negative medullary thyroid cancer that had an aggressive recurrence, presenting with superior vena cava syndrome, and managed with multimodality treatment in the form of radiotherapy and cytotoxic chemotherapy for local control and palliation. RESULTS A 53-year-old man presented with a 20-year history of a gradually enlarging anterior neck mass, initially noted as a marble-shaped lesion. Six months prior to consult, the patient observed a marked increase in the size of the mass along with a palpable lymph node on the left side of the neck. The patient underwent total thyroidectomy with radical neck dissection. Histopathology revealed a well-differentiated medullary thyroid carcinoma with lymphovascular invasion. Immunohistochemical staining was positive for calcitonin. Serum carcinoembryonic antigen (3.11 ng/mL, normal value <3.00) and calcitonin (<2.00 pg/mL, normal value 0 to 18.20) were both normal. The patient noted multiple, enlarging neck masses four months after surgery. Radiotherapy was administered for a total of 25 Gy in five fractions. Cytotoxic chemotherapy with cyclophosphamide, vincristine, and dacarbazine was initiated. The combination of radiotherapy and cytotoxic chemotherapy were considered viable treatment modalities in the pursuit of local control and palliation of this unusually aggressive disease. CONCLUSION This case demonstrates how non-surgical management through multiple modalities can be utilized for local control and palliation of this aggressive disease. Therapeutic options may be limited in the developing world especially when a tumor is at its advanced stage, but much can still be done for the holistic care of the cancer patient.